Customer Perceptions of Sustainable Goat Cheese Production Within a Circular Farm to Fork Model: a Case Study of PIB College - Sandy Dwiputra Yubianto (INSPIRE : Journal of Culinary, Hospitality, Digital & Creative Arts and Event, 2025)
The rapid growth of the food industry has increased the significance of culinary education, particularly in promoting sustainable practices. At Politeknik Internasional Bali (PIB), sustainability is a key focus in both practical teaching and food production. The campus’s farm, which raises goats and Balinese oxen, provides an opportunity to incorporate locally sourced goat cheese into the menu of the campus restaurant. The farm-to-fork concept emphasizes the use of local, sustainable ingredients, aligning with the principles of responsible consumption and reducing the environmental impact of food systems. Additionally, the culinary arts program at PIB addresses food waste by repurposing waste from student practicals as feed for the goats, contributing to a more sustainable and circular food production system. This research aims to assess the customer perception, focusing on how sustainability performed through campus-sourced goat cheese perceived by the eyes of consumer. The study resulted that consumers will respond favorably to the Farm to Fork approach, viewing it as an attractive and eco-friendly option. By highlighting the sustainability of local production and reducing waste, the research explores how Farm to Fork strategies can encourage and enhance responsible food consumption.